THE CORRELATION BETWEEN TRANSLATION ABILITY AND READING HABIT TOWARD WRITING ABILITY - Darmawan Budiyanto (Jurnal Didascein Bahasa, 2019)
This research is aimed to find out the correlation between (1) translation ability and writing ability; (2) reading habit and writing ability; (3) translation ability and reading habit toward writing ability. The population of the study was the fourth semester in the academic year 2019/2020. The sampling technique used is convenience non random sampling. The researcher used test to obtain the data of students’ translation ability, then questionnaire to obtain the data of students’ reading habit level and test to obtain the data of students’ writing ability. Theresearcher used Product Moment formula to know the coefficient correlation and linear regression to find out the significance correlation. There three results of the study, fist hypothesis, showed that the coefficient of correlation between students’ translation ability (X1) and their writing ability (Y) is higher than 0 (0.9083>0) and linear regression showed that t obtain is higher than t table (10.415 > 2.069). Second hypothesis, showed that the coefficient of correlation between students’ reading habit (X2) and their writing ability (Y) is higher than 0 (0.6939>0) and linear regression showed that t obtain is higher than t table (4.621 > 2.069). Furthermore, the third hypothesis showed that the coefficient of correlation (ryx1x2) between students’ translation ability (X1) reading habit (X2) and their writing ability (Y) is higher than 0 (0.8304>0) and linear regression showed that t obtain is higher than t table (24.443 > 3.44). It means translation ability and reading habit is a good predictor for the students’ writing ability.